Pengembangan Penuntun Praktikum Berbasis Argument Driven Inquiry untuk Siswa Kelas VII di SMP/MTs - Ummi Abdani Utari; Leni Marlina; Eni Yulianti (Pendidikan Biologi STKIP YPM Bangko, 2020)
This research was motivated by the absence of a practicum guide that explains practicum activities, especially regarding life organizational systems. For practicum guidance, science teachers only take from student worksheets. Than why conceptual, practical, and real practicum guides development is needed. One of which is practicum guides based on Argumen Driven Inquiry. Focus on subject life organization systems for students of Class VII SMP / MTs. The purpose of this research is to produce a valid based on Argumen Driven practicum guide. This researchh is a development research using 4.D which is modified including the stages of define, design, develop, and disseminate. This study consisted of 7 validators. Based on the results of this study, a valid Argument Driven Inquiry based practical guide was produced. The practicum guide produced was declared very valid by the validator, both from the aspects of contents peasibility,language, presentation,and graphics with a value of 94%. From the research result that have been obtained it can be concluded that based on Argumen Driven Inquiry the practicum guide (ADI) in science learning on subjetc life organization system material is declared valid.